The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/bmjopen-2020-040878
|View full text |Cite
|
Sign up to set email alerts
|

Disease composition and epidemiological characteristics of primary care visits in Pudong New Area, Shanghai: a longitudinal study, 2016–2018

Abstract: ObjectivesThis study aims to analyse the disease composition of primary care visits rather than specialist visits, the former of which had scarcely been studied. We adopted specific disease classification (International Statistical Classification of Diseases and Related Health Problems, 10th Revision), disease system and communicable/non-communicable/injury disease classification, and variations of sex and age were also analysed.SettingWe extracted data from all community health service centres (CHSCs) and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, the study identified acute upper respiratory tract infections as the most prevalent health issue seen in primary care facilities (6.67%), followed by chronic conditions like hypertension and diabetes mellitus (Chen et al, 2022). Similar findings were reported by other studies as well (Adib et al, 1995;Gong et al, 2020). In Qatar, primary healthcare services are administered through a network of healthcare centres.…”
Section: Introductionsupporting
confidence: 83%
“…Furthermore, the study identified acute upper respiratory tract infections as the most prevalent health issue seen in primary care facilities (6.67%), followed by chronic conditions like hypertension and diabetes mellitus (Chen et al, 2022). Similar findings were reported by other studies as well (Adib et al, 1995;Gong et al, 2020). In Qatar, primary healthcare services are administered through a network of healthcare centres.…”
Section: Introductionsupporting
confidence: 83%
“…Therefore, identifying major diseases and some prominent problems, focusing on key groups in the region allow an effective way for the government, society and public work together to promote health. We found that NCDs accounted for 49.04% of all diseases, and although their proportion is still much lower than that in developed regions of China, 19 they have become a major public health challenge in Dongfang. It is worth nothing that the proportion of the population aged 65 years or older in 2020 has increased by 2.99% compared with 2010, while the proportion of the population aged 15–59 years has decreased by 2.66%.…”
Section: Discussionmentioning
confidence: 78%
“…1, the group of 40-64 had the largest proportion of patient visits each year, followed by elderly group aged 65 or above, the group of 19-39, the group of 6-12 and the group of 0-5. The age group of [13][14][15][16][17][18] had the lowest proportion of visits.…”
Section: Characteristics Of Primary Care Settingsmentioning
confidence: 99%
“…Such understanding should help develop strategic reactions of the system to deal with pandemic situations to avoid system collapse. Literature shows that existing global studies have addressed primary care service utilization of patients in general or with speci c characteristics, or in relation to the service infrastructure, component, in uential factors and quality [17][18][19][20][21][22][23][24]. In the background of Chinese health system characteristics and Covid 19 pandemic situations, the current study was conducted from a more general perspective to describe a local primary care system, its patient encounters and disease pro les of the patients within an integrated health organization in a rural town in southern China.…”
Section: Introductionmentioning
confidence: 99%